Vamos saravá! As tradições religiosas afro-brasileiras na obra de Clementina de Jesus - Silva, Camila Luiza Souza da (2017)
This work aims at settling out a dialogue between the Afro-Brazilian religions and the samba. A historical-anthropological approach. In this regard, this analysis will be based on works by Clementina de Jesus. Clementina de Jesus was born in the region known as Paraiba Valley in Rio de Janeiro State. Clementina would represent the black people from the communities which have been regarded as the co-founders of the Samba Schools – communities such as: “Salgueiro”, “Serrinha” and “Mangueira”. Furthermore, Clementina’s albums are not only filled with sambas, but also ‘jongos’, ‘partidos-altos’, ‘pontos’ and ritual songs that have been recreated from Afro-Brazilian religions. Therefore, Clementina can be considered as a linking point between the ethnical groups known, in general terms, as “Sudanese people” and “Bantu people”. These ethnical groups brought a lot of richness to Brazilian both culture and religions. Besides that, the singer represents the remaining tension in the History of Samba: it was necessary to keep samba aside from its percursive dimension so that it would be more palatable to the ears of middle class, and, consequently, accepted by the radio industry – although this musical genre has its Afro-Brazilian roots widely acknowledged. Clementina’s pieces of work – which have been stongly influenced by the - Afro-Brazilian religious universe – problematize both Brazilian structural racism and the question of “deafricanization” in samba. By doing this work, I intend to study the attempt of removal of the samba from Afro-Brazilian religions as well as its musical structure imposed by the recording industry. In this sense, by analyzing the works by Clementina, questions will be raised to foster a debate about the theme.